Assessment of four genotypes of cacao in Nariño, Colombia - Bacca , Pedro Pablo; Alarcon, Karen Andrea; González, Juan Carlos; Guzmán, Félix Alberto; Coronado, Roberto Antonio; Romero Barrera, Yajaira (Revista Mexicana de Ciencias Agrícolas, 2023)
The cacao (Theobroma cacao L.) crop for the department of Nariño represents a productive alternative to the substitution of illicit crops, on which small and medium producers depend; nevertheless, high relative humidity, temperature, and rainfall, as well as inadequate phytosanitary management, cause a high incidence of diseases such as Moniliophthora roreri and Phytophthora sp., limiting productive yield. In this sense, it is necessary to identify cacao clones adapted to the conditions of the area and tolerant to the main diseases. This study aimed to assess the productive and sanitary potential in the initial stages of development of four cacao clones, TCS 01, TCS 06, TCS 13, and TCS 19, under environmental conditions of the Nariño Pacific. The SAS 9.4 software was used for the statistical analysis, employing the Glimmix procedure to analyze the variables, and the analysis was adjusted to the Poisson distribution. In addition, Tukey’s tests were used when there were significant differences. The clone TCS 19 presented the best results in production (1.44 kg dried bean tree-1), surpassing the commercial control ICS 95 (0.6 kg dried bean tree-1). In terms of health, M. roreri was the disease with the highest incidence, especially in the genotypes TCS 01 (38.67%) and TCS 13 (25.85%). The yields of the materials evaluated exceeded the average national (460 kg ha-1) and regional (560 kg ha-1) production. According to these results, TCS 19 could potentially be considered a promising genetic resource for the development of cacao farming on the Pacific Coast of Nariño.
Keywords: Afro-Colombian; agroforestry; crops; plant health; productivity